Southern Ocean Decadal Variability and Predictability - Latif, Mojib; Martin, Torge; Reintges, Annika; Park, Wonsun (Current Climate Change Reports, 2017)
The Southern Ocean featured some remarkable changes during the recent decades. For example, large parts of the Southern Ocean, despite rapidly rising atmospheric greenhouse gas concentrations, depicted a surface cooling since the 1970s, whereas most of the planet has warmed considerably. In contrast, climate models generally simulate Southern Ocean surface warming when driven with observed historical radiative forcing. The mechanisms behind the surface cooling and other prominent changes in the Southern Ocean sector climate during the recent decades, such as expanding sea ice extent, abyssal warming, and CO2 uptake, are still under debate. Observational coverage is sparse, and records are short but rapidly growing, making the Southern Ocean climate system one of the least explored. It is thus difficult to separate current trends from underlying decadal to centennial scale variability. Here, we present the state of the discussion about some of the most perplexing decadal climate trends in the Southern Ocean during the recent decades along with possible mechanisms and contrast these with an internal mode of Southern Ocean variability present in state-of-the art climate models.